Analysis the Influence of Interest Rates on Inflation Rate Developments - Nurul Anisa; Zaqia Yuliana Pratiwi; Farhana Talida Kamila; Rayhan Ananta; Andrie Sheva Faturrahman; Dahri Tanjung; Disya Ayu Rivtryana (International Journal Business, Management and Innovation Review, 2024)
Inflation is an increase in the overall prices of goods and services that occurs continuously. The aim of this research is to analyze the influence of interest rates on the development of the inflation rate. Interest rates are one of the monetary policy instruments used by central banks to control inflation. Inflation is an indicator that reflects economic health and influences various aspects such as purchasing power, monetary policy and economic stability. This research examines the effect of changes in interest rates as the main monetary policy instrument used to control inflation and its impact on economic growth. The method used in this research is simple linear regression to analyze the data. The research results show that the coefficient of determination (R2) is 0.169. This means that around 16.9% of the Inflation variable (Y) is influenced by the independent variable, namely Interest Rates (X). Researchers found that in determining monetary policy the central bank has two quick decision options to control the stability of the inflation rate, including, increasing interest rates when the inflation rate is high or reducing interest rates when the inflation rate is decreasing which results in sluggish economic activity.